When Newsroom Tears Go Viral: A Sentiment Analysis of Public Response to Media Layoffs in Indonesia - Assyari Abdullah; Dwi Sutri Astuti; Edison Edison; Mustafa Mustafa; Muhammad Soim; Yefni Yefni; Yasril Yazid; Jayus Jayus; Sumaiyah Sumaiyah; Sofiyanita Sofiyanita; Akmal Khairi (Jogjakarta Communication Conference (JCC), 2026)
The recent phenomenon of layoffs (PHK) in the Indonesian media industry has triggered an emotional public response, especially when the event involves figures who have built close relationships with audiences. This study aims to analyze public sentiment towards the viral farewell moment of KompasTV presenter Gita Maharkesri, as a symbol of the humanitarian crisis in the media workplace. Data was collected from 2,238 user comments on the Antaranews YouTube video using a crawling technique using the YouTube Data API v3 and analyzed using a Python-based Big Data Analytics approach in Google Colab. The results show that the majority of comments are neutral (73.1%), followed by positive comments (14.1%) and negative comments (12.8%). Positive comments reflect a strong parasocial relationship, characterized by words such as "semangat," "terima kasih," and "terembus," while negative comments are often critical of the media presentation, with keywords such as "exaggerated," "PHK," and "bohong." The temporal distribution shows a spike in interactions in the first two days after the video aired, then a gradual decline. Correlation analysis between words reveals clusters of discourses of empathy and criticism coexisting. This study concludes that public responses to media layoffs are not merely emotional but also reflect a social awareness of job instability in the digital age. These findings underscore the importance of ethical and empathetic crisis communication in the new media landscape and demonstrate the crucial role of sentiment analysis as a tool for understanding collective public opinion.